Решите уравнение : (х-3)(хв квадрате+3х+9)-х(х в квад-16)=21, 16х(4х в кв-5)+17=(4х+1)(16х в кв -4х+1)

Пушка1244 Пушка1244    1   29.03.2019 09:50    0

Ответы
катяипапа000111 катяипапа000111  27.05.2020 11:54

(x-3)*(x^2+3*x+9)-x*(x^2-16) = 21

(x-3)*(x^2+3x+9)-x*(x^2-16)=16x-27 (преобразование для левой части уравнения)

16x-27=3*7

16x-27=21

16x=48(16 удаляем)

x=3

16Х(4Х^2-5)+17=(4Х+1)(16Х^2-4Х+1)

16x*(4x^2-5)+17=64x^3-80x+17

64x^3-80x+17=(4x+1)(16x^2-4x+1)

x=1/5

Где "^" - степень

 

 

 

 

 

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра